Against technology-mediated personalized learning: resources from John William Miller and Henry Bugbee to support parental resistance. Issue 1 (2nd January 2020) - Frank, Jeff
ABSTRACT: This paper aims to provide parents and others resources to resist technology-mediated personalized learning. To develop these resources and make the case against technology-mediated Â personalized learning, I turn to the work of American philosophers Henry Bugbee and John William Miller.